To solve for x in the equation x - 9/4 = -3/8, we can start by subtracting -9/4 from both sides of the equation:
x - 9/4 + 9/4 = -3/8 + 9/4
Simplifying, we get:
x = (9/4) - (3/8)
To add these fractions, we need the same denominator. We can convert 9/4 to the equivalent fraction with a denominator of 8:
x = (9/4) * (2/2) - (3/8)
Multiplying the numerators and denominators:
x = 18/8 - 3/8
Now that the fractions have the same denominator, we can subtract the numerators:
x = (18 - 3)/8
x = 15/8
Therefore, x = 15/8.
what is x? x-9/4=-3/8
1 answer